Research on the Evaluation of Dynamic Mathematics Software Based on User Experience - Wang, Jie; Zhang, Linjing; Li, Chuanzhong; Cai, Ruiqi; Chen, Wanwei; Rao, Yongsheng (International Conference on Computer Science & Education, 2020)
Dynamic mathematics software (DMS) is widely used in teaching, which improves the efficiency of teaching and learning. How to evaluate DMS from a scientific perspective has become one of the problems in the integration of information technology and education. In this paper, based on user experience theories, we construct the evaluation model named CCEMS (clarity, credibility, efficiency, motivation and subject). Then, according to theories related of DMS, Delphi method and Analytic Hierarchy Process (AHP), we construct an evaluation index system of DMS. Finally, the system is applied into the Geometer's Sketchpad (GSP) and NetPad to analyze their advantages and disadvantages. The results show that user experience score of NetPad is better than GSP, which indicates that NetPad can better meet the needs of users.